Effect of Monetary Policy on Macro Economic Variables of Nepal - Basnet, Nirajan (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
This study examines the effect of monetary policy on macroeconomic variables such as gross domestic product, real interest rate, inflation, unemployment and balance of payment etc. All the variables are intertwined with each other, and one way or the other it affects each other in both short run and long run. It is secondary research with causal comparative research design. It has quantitative nature and time series data are extracted from year 1990 to 2017 of six different macro-economic variables for the study. Statistical tools and applied econometrics namely, descriptive statistics, ADF, Johansen cointegration test, Engle- Granger error correction model are applied. The result from the statistical analysis shows that instruments of monetary policy has influence on the selected macroeconomic variables to some extent and satisfies to be relatively effective. Findings of the study reveals that there is long-run relationship between monetary policy and the selected macroeconomic variables in the Nepalese economy significantly from the error correction mechanism.